Improve Network Performance By Enabling Explicit Congestion Notification (ECN) In SCTP Control Chunks - Elhalabi, Mohammed J. M. (2008)
Recently in communication community, and because of the need to a reliable transmission protocol, that can cover the Transport Control Protocol (TCP) and User Datagram Protocol (UDP) lacks, the Internet Engineering Task Force (IETF) defined a new protocol called Stream Control Transmission Protocol (SCTP). As new as SCTP is, as important to do experiment on it, therefore, this dissertation proposes adding Explicit Congestion Notification (ECN) mechanism into SCTP chunks (INIT chunk, and INIT-ACK chunk) to improve the delay of transferring important data during congestion, where illustrates the benefit of SCTP compared with the previous protocols Transmission Control Protocol (TCP) and User Datagram Protocol (UDP), then discuss the details of adding ECN, and the reason behind Random Early Detection (RED) choice. Through the experimental analysis, we compare SCTP enabled ECN in INIT-ACK chunk to SCTP non ECN enabled in INIT-ACK chunk, and demonstrate the result of ECN impact on SCTP delay time.